Proceedings of the 11th Working Conference on Mining Software Repositories 2014
DOI: 10.1145/2597073.2597118
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis of commit comments in GitHub: an empirical study

Abstract: Emotions have a high impact in productivity, task quality, creativity, group rapport and job satisfaction. In this work we use lexical sentiment analysis to study emotions expressed in commit comments of different open source projects and analyze their relationship with different factors such as used programming language, time and day of the week in which the commit was made, team distribution and project approval. Our results show that projects developed in Java tend to have more negative commit comments, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(127 citation statements)
references
References 4 publications
2
115
1
2
Order By: Relevance
“…Their research identified relationships between positive and negative sentiment and factors such as the programming language used, team members' geographic locations, day of the week and project approval [14]. Like Guzman et al we apply sentiment analysis to the messages left behind during the development process, but focused our approach on the comparisons of projects using TDD process with those not using TDD process.…”
Section: B Sentiment In Software Artifactsmentioning
confidence: 99%
“…Their research identified relationships between positive and negative sentiment and factors such as the programming language used, team members' geographic locations, day of the week and project approval [14]. Like Guzman et al we apply sentiment analysis to the messages left behind during the development process, but focused our approach on the comparisons of projects using TDD process with those not using TDD process.…”
Section: B Sentiment In Software Artifactsmentioning
confidence: 99%
“…This three metrics have been used by other researchers, i.e., politeness [23] and [24], sentiment [25] and [26], and emotion [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sentiment polarity analysis has been recently applied in the software engineering context to study commit comments in GitHub [9], GitHub discussions related to security [10], productivity in Jira issue resolution [11], activity of contributors in Gentoo [12] and evolution of developers' sentiments in the openSUSE Factory [13]. It has also been suggested when assessing technical candidates on the social web [14].…”
Section: Introductionmentioning
confidence: 99%